2023
DOI: 10.3390/microorganisms11051176
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Multidrug-Resistant Mutants Derived from Heterologous Expression Chassis Strain Streptomyces albidoflavus J1074

Abstract: Streptomyces albidoflavus J1074 is a popular platform to discover novel natural products via the expression of heterologous biosynthetic gene clusters (BGCs). There is keen interest in improving the ability of this platform to overexpress BGCs and, consequently, enable the purification of specialized metabolites. Mutations within gene rpoB for the β-subunit of RNA polymerase are known to increase rifampicin resistance and augment the metabolic capabilities of streptomycetes. Yet, the effects of rpoB mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Its small genome, capacity to produce versatile precursors, and dispersed mycelial growth compared to other Streptomyces, make it one of the most convenient Streptomyces production host to scale up in industrial bioreactors (Marín et al, 2017; Myronovskyi & Luzhetskyy, 2019; Zaburannyi et al, 2014). However, the production yields are often low, requiring tedious chassis optimization and/or production processes (Dolya et al, 2023; Gummerlich et al, 2021; Li et al, 2023). Genome-wide studies and characterization of the TRN in other Streptomyces has identified regulators, promoter regions, and transcription start sites, which may improve rational strain design decisions and production yield (Hwang et al, 2019; Jeong et al, 2016; Luo et al, 2018; Yi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its small genome, capacity to produce versatile precursors, and dispersed mycelial growth compared to other Streptomyces, make it one of the most convenient Streptomyces production host to scale up in industrial bioreactors (Marín et al, 2017; Myronovskyi & Luzhetskyy, 2019; Zaburannyi et al, 2014). However, the production yields are often low, requiring tedious chassis optimization and/or production processes (Dolya et al, 2023; Gummerlich et al, 2021; Li et al, 2023). Genome-wide studies and characterization of the TRN in other Streptomyces has identified regulators, promoter regions, and transcription start sites, which may improve rational strain design decisions and production yield (Hwang et al, 2019; Jeong et al, 2016; Luo et al, 2018; Yi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The production of secondary metabolites appear to mainly stem from the activation of biosynthetic gene clusters (BGCs) through a hierarchical network of transcriptional regulators in response to various internal and external signals, such as nutrient availability, stress, and intercellular communication (Barbuto Ferraiuolo et al, 2021; Chen et al, 2010; Wohlleben et al, 2017; Xia et al, 2020; Zhang et al, 2020). However, many BGCs remain silent or poorly expressed under standard laboratory conditions, limiting the discovery and production yield of desired compounds (Dolya et al, 2023). While several strategies have been developed to activate and optimize BGC expression, such as genome editing, heterologous expression, co-cultivation, and elicitor addition, the TRN of Streptomyces is poorly understood compared to other model bacteria, which limits the potential and applicability of rational strain design (Barbuto Ferraiuolo et al, 2021; Chater, 2016; Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation